Reimagining Disability and Inclusive Education Through Universal Design for Learning - Wilson, Jan Doolittle (Disability Studies Quarterly, 2017)
In 1975, Congress enacted a law eventually known as the Individuals with Disabilities Education Act (IDEA), which ensures that children with disabilities receive a free, appropriate, public education. Since then, scholarly and popular debates about the effectiveness of inclusive education have proliferated and typically focus on the ability or inability of students with disabilities to succeed in so-called regular classrooms. These debates reflect widespread assumptions that the regular classroom is rightly the province of nondisabled students and a neutral, value-free space that students with disabilities invade and disrupt via their very presence and their costly needs for adaptation. But as many scholars in the field of Disability Studies in Education (DSE) have argued, these discussions often fail to recognize that the space of the regular classroom, far from neutral, is constructed for a nondisabled, neurotypical, white, male, middle-class "norm" that neither reflects nor accommodates the wide range of diverse learners within it, regardless of whether these learners have been diagnosed with a disability. A DSE perspective sees the educational environment, not students with disabilities, as the "problem" and calls for a Universal Design for Learning approach to education, or the design of instructional materials and activities that allows the learning goals to be achievable by individuals with wide differences in their abilities and backgrounds. Agreeing with this DSE perspective, this article uses an autoethnographic approach to reexamine inclusive education and to consider how university classrooms, pedagogy, and curricular materials can be improved in order to accommodate all students, not just those with disabilities. Ultimately, the article argues that Universal Design for Learning has the potential to radically transform the meaning of inclusive education and the very concept of disability.